Polarized optical transmittance spectra of nonlinear thiogallate crystals near "isotropic point" - Kushnir, O.S.; Dzendzelyuk, O.S.; Hrabovskyy, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The results of researches of the polarized optical transmittance spectra of
nonlinear thiogallate crystals near the “isotropic point” are represented and discussed